2013
DOI: 10.1111/j.1439-0418.2010.01568.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of post‐teneral diets on the performance of sterileAnastrepha ludensandAnastrepha obliquafruit flies

Abstract: The effect of post‐teneral diets on the mating performance, pheromone production and longevity of sterile Anastrepha ludens and Anastrepha obliqua fruit flies (Diptera: Tephritidae) was investigated. Enriched pre‐release diets improved male mating performance. Wild and sterile males fed on mango and orange fruits achieved the greatest copulatory success, followed by those fed on a 3 : 1 sugar : yeast (SY) diet. Males fed only on a sugar diet achieved the lowest number of matings. The mean numbers of copulas ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 70 publications
0
62
0
Order By: Relevance
“…First, pheromone output might be influenced by diet quality and the accumulation of specific macro (South et al, 2011) or micro (Kopena et al, 2014) nutrients. In these cases, individuals consuming a high quality diet typically increase pheromone output, leading to a more conspicuous, and/or attractive signal (Liedo et al, 2013). Second, components of the pheromone that cannot be synthesized entirely de novo might be sequestered from dietary sources and then transformed, or directly incorporated into the pheromone (Blaul et al, 2014).…”
Section: Dietary Influences On Pheromone Profiles and Signature Mixturesmentioning
confidence: 99%
See 2 more Smart Citations
“…First, pheromone output might be influenced by diet quality and the accumulation of specific macro (South et al, 2011) or micro (Kopena et al, 2014) nutrients. In these cases, individuals consuming a high quality diet typically increase pheromone output, leading to a more conspicuous, and/or attractive signal (Liedo et al, 2013). Second, components of the pheromone that cannot be synthesized entirely de novo might be sequestered from dietary sources and then transformed, or directly incorporated into the pheromone (Blaul et al, 2014).…”
Section: Dietary Influences On Pheromone Profiles and Signature Mixturesmentioning
confidence: 99%
“…Numerous studies demonstrate a role of diet quality for mate assessment pheromones across a wide range of taxa, including insects (Shelly et al, 2007;South et al, 2011;Fedina et al, 2012;Weddle et al, 2012;Liedo et al, 2013); mammals (Ferkin et al, 1997;Havlicek and Lenchova, 2006); reptiles (Kopena et al, 2011(Kopena et al, , 2014Chouinard, 2012); arachnids (Cross et al, 2009;Baruffaldi and Andrade, 2015); and fish (Giaquinto, 2010;Giaquinto et al, 2010;Hayward and Gillooly, 2011 ; Table 1). Nonetheless, comprehensive studies that include both behavioral and chemical assays are largely limited to insect systems.…”
Section: Linking Diet and Individual Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…On the day of emergence, adults were separated by categories (males from the Tap-7 strain, females from the bisexual strain, wild males, and wild females) and confined in similar cages, each 1 containing 100 individuals. Adults were fed sugar with hydrolyzed protein (MP Biomedicals, LLC, Santa Ana, California) at a ratio of 24:1 (Liedo et al 2013). Flies were kept under laboratory conditions at 24.0 °C ± 1.5, 70.5 ± 10.0% relative humidity with fluorescent light for 12 hr (850 ± 110 lux, 7 AM to 7 PM) followed by 12 hr of darkness.…”
Section: Insectsmentioning
confidence: 99%
“…In addition to aromatherapy, providing food supplements during the adult stage has also shown promising results. Liedo et al, (2010), for example, demonstrated that both wild and sterile A. obliqua males fed with mangoes and oranges showed greater mating success than flies fed on normal diets (yeast + sugar). Pérez-Staples et al, (2009) found that sterile males of Bactrocera tryoni (Froggatt) that fed on yeast hydrolysate for a brief period were as competitive as wild males.…”
Section: Discussionmentioning
confidence: 99%